New Twists in Ovarian Stimulation and Their Practical Implications - Pirtea, Paul; de Ziegler, Dominique; Poulain, Marine; Ayoubi, Jean Marc (Frontiers in Medicine, 2019)
Ovarian stimulation (OS) has for objective to induce multiple ovulation in order to facilitate a multiple oocyte harvest and offer multiple embryos available for transfer thereby increasing the efficacy of ART. Originally, the primary fear that existed was the occurrence of frank ovarian hyperstimulation syndrome (OHSS), a possibly dreadful – sometime fatal – complication of ART. These fears limited the number of oocytes aimed for during OS in order to control what the risk of OHSS. On the contrary, the meager implantation rates of the early days of ART led to easily transfer multiple embryos in order to achieve acceptable pregnancy rates. Today the perspectives have changed. The advent of antagonist-based OS protocol and the possibility to trigger the ultimate phase of oocyte maturation with GnRH-a has allowed to make the risk of OHHS a worry of the past. On the contrary the markedly increased implantation rates of today’s ART makes multiple pregnancy a worry that has come in the limelight worldwide, pushing the practice of single embryo transfer (SET).